2021
DOI: 10.1002/humu.24162
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in KIF7 implicated in idiopathic scoliosis in humans and axial curvatures in zebrafish

Abstract: Idiopathic scoliosis (IS) is a spinal disorder affecting up to 3% of otherwise healthy children. IS has a strong familial genetic component and is believed to be genetically complex due to significant variability in phenotype and heritability. Previous studies identified putative loci and variants possibly contributing to IS susceptibility, including within extracellular matrix, cilia, and actin networks, but the genetic architecture and underlying mechanisms remain unresolved. Here, we used whole‐exome sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 73 publications
(109 reference statements)
3
29
0
Order By: Relevance
“…Defects in cilia, microtubule-based projections critical for cell signaling and fluid flow, have been linked to scoliosis in animal models [ 31 , 34 , 35 , 37 , 94 , 95 ]. A variant in the ciliary kinesin KIF7 was found within one AIS family and specific KIF7 mutations produced scoliosis in zebrafish [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defects in cilia, microtubule-based projections critical for cell signaling and fluid flow, have been linked to scoliosis in animal models [ 31 , 34 , 35 , 37 , 94 , 95 ]. A variant in the ciliary kinesin KIF7 was found within one AIS family and specific KIF7 mutations produced scoliosis in zebrafish [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing studies (i.e., whole exome sequencing) both within families and unrelated individuals with AIS have identified rare variants in extracellular matrix genes that may contribute to the AIS phenotype [ 28 , 29 , 30 ]. Recent genetic and functional studies have led to varied hypotheses of AIS etiology, including dysfunction within neuroinflammatory pathways [ 31 , 32 ], the cartilage matrisome [ 33 ], cilia, the cytoskeleton [ 34 , 35 , 36 , 37 , 38 ], or the vestibular system [ 39 , 40 , 41 , 42 , 43 ]. However, the inability thus far to relate specific genetic variants to the biology of AIS and the wide variation in which AIS presents are indicative of the complex heterogeneity of this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, knockout of Kif7 is perinatal lethal with early embryonic defects, including preaxial polydactyly, exencephaly, agenesis of the corpus callosum, and microphthalmia (Endoh-Yamagami et al, 2009;Cheung et al, 2009;Putoux et al, 2019). In fish, knockdown of KIF7 function results in altered Hedgehog pathway gene expression, disruption of left-right asymmetry and scoliosis (Wilson et al, 2009;Maurya et al, 2013;Terhune et al, 2020;Liang et al, 2020). In humans, mutations in KIF7 have been shown to cause severe ciliopathies, including Joubert, hydrolethalus, acrocallosal, Meckel-Gruber and Bardet-Biedl syndromes (Ali et al, 2012;Barakeh et al, 2015;Bachmann-Gagescu et al, 2015;Karaer et al, 2015;Putoux et al, 2011Putoux et al, , 2012Tunovic et al, 2015;Walsh et al, 2013;Ibisler et al, 2015;Dafinger et al, 2011;Asadollahi et al, 2018;Subramanian et al, 2019;Liang et al, 2020;Terhune et al, 2020;Dahl et al, 2020;Niceta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In fish, knockdown of KIF7 function results in altered Hedgehog pathway gene expression, disruption of left-right asymmetry and scoliosis (Wilson et al, 2009;Maurya et al, 2013;Terhune et al, 2020;Liang et al, 2020). In humans, mutations in KIF7 have been shown to cause severe ciliopathies, including Joubert, hydrolethalus, acrocallosal, Meckel-Gruber and Bardet-Biedl syndromes (Ali et al, 2012;Barakeh et al, 2015;Bachmann-Gagescu et al, 2015;Karaer et al, 2015;Putoux et al, 2011Putoux et al, , 2012Tunovic et al, 2015;Walsh et al, 2013;Ibisler et al, 2015;Dafinger et al, 2011;Asadollahi et al, 2018;Subramanian et al, 2019;Liang et al, 2020;Terhune et al, 2020;Dahl et al, 2020;Niceta et al, 2020). Recent work has suggested that KIF7 also plays a role in cell proliferation during development and disease (Coles et al, 2015;Wong et al, 2017;Lau et al, 2017;Hu et al, 2020;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional genetic association methods including familial linkage studies [7][8][9][10][11][12][13][14][15][16][17], exome sequencing [18][19][20][21][22][23][24][25][26][27], and genome wide association studies (GWAS) [28][29][30][31][32][33][34][35][36] have resulted in a number of positive associations with IS, of which only a few loci, notably those in or near ADGRG6 [31,[37][38][39][40][41][42][43] and LBX1 [21,29,30,[44][45][46][47][48][49][50][51][52]…”
Section: Introductionmentioning
confidence: 99%